2016
DOI: 10.1038/ki.2015.333
|View full text |Cite
|
Sign up to set email alerts
|

In a retrospective international study, circulating miR-148b and let-7b were found to be serum markers for detecting primary IgA nephropathy

Abstract: Immunoglobulin A nephropathy (IgAN) is a worldwide disease characterized by the presence of galactose-deficient IgA1 deposits in the glomerular mesangium. A kidney biopsy for diagnosis is required. Here, we measured two miRNAs (let-7b and miR-148b), previously identified as regulators of the O-glycosylation process of IgA1, in serum samples from patients with IgAN and healthy blood donors (controls) recruited in an international multicenter study. Two predictive models, based on these miRNAs, were developed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 45 publications
0
60
2
Order By: Relevance
“…A selection bias was present in this study. Patients experienced rather milder renal impairment compared to similar studies in IgA by other scholars [40,51]. This could explain why we did not observe much glomerular sclerosis instead of IFTA lesions, which was also an additional reason for our lack of outcome event observations.…”
Section: Discussioncontrasting
confidence: 42%
“…A selection bias was present in this study. Patients experienced rather milder renal impairment compared to similar studies in IgA by other scholars [40,51]. This could explain why we did not observe much glomerular sclerosis instead of IFTA lesions, which was also an additional reason for our lack of outcome event observations.…”
Section: Discussioncontrasting
confidence: 42%
“…Two miRNAs, miR-148b and let-7b, which seem to mediate the aberrant O-glycosylation process of IgA and that can differentiate IgA nephropathy patients in serum tests5960, were not significantly expressed in our cohort. In other diseases like in acute leukemia or gastric cancer it has been shown that serum levels of miRNA expression were not the same as in tissue samples6162.…”
Section: Discussionmentioning
confidence: 60%
“…A large number of studies [36-38] comfirm that miRNAs can be biomarkers of IgA nephropathy, such as miR-148b, let-7b, miR-3613-3p, miR-200a, miR-200b, and so on. Due to being non-invasive and easily obtained, urinary sediment miRNAs have become a new direction for searching for non-invasive biomarkers of IgAN.…”
Section: Erythrocyte-derived Mirnas Can Be Specific Biomarkers Of Iganmentioning
confidence: 99%